SECONDARY STUDENTS’ REFLECTION TOWARDS MULTIMODAL READING TASKS THROUGH VIRTUAL DIGITAL PLATFORM LEARNING DURING THE COVID-19 PANDEMIC: VOICES FROM INDONESIA - Hikmah Pravitasari; Royhan Kamal (English Didactic, 2022)
This study reports on secondary students’ reflection towards multimodal reading tasks through virtual digital platform learning. It investigates students’ learning outcomes after studying a multimodal reading involving through five-step learning activities, such as lesson preparation to examine the lesson-planning process, including the use of supplementary materials, and the meaningfulness of activities, scaffolding/modeling to focus on making explicit and direct links between past learning related to the students’ schemata and new concepts, comprehensible input to consider adjusting teacher modeling multimodal reading to enhance comprehension, practice and application  and review and assessment to assess students’ learning, and provided feedback to students on their output The data were collected during the 2nd academic term (January-May 2020). The research was conducted in the Senior High School in Indonesia in which thirty five students (20 females and 15 males)  participated in this study. The data were analyzed by using Braun Clark’s (2006) thematic analysis.  The findings show that encountered some benefits from this digital platform learning such as the availability of myriad sources online which the students could access at their flexible and convenience time. Additionally, Student teachers’ autonomy, agency, engagement, confidence, skill-set, and the ability to collaborate through online discussion are the important point that they experienced during their learning reading digital texts. Finally, the short time of the studies included in exploration might also indicate the strong need for further longitudinal research on the topic.